Native language interference in learning english as a foreign language: an analysis of written material produced by spanish speaking students in senior high school classes - Moncayo, Anita (2010)
Even though the learner shows a good knowledge of the target language, there is a sort of linguistic interference of the native language; it seems that the native language exerts great influence on the second and foreign language learning and use, as it has been observed in previous studies on this topic made by researchers as Ellis, Krashen, Lightbown, Spada, Schütz, Baljit, Nunan, and others. This research is aimed to describe and analyze some specific aspects of grammar and vocabulary use in english as foreign language writing and to find out the level of interference of Spanish linguistic habits in english performance.